Effect of combined surface treatments on surface roughness and resin bond strength to Y-TZP ceramic and nickel-chromium metal alloy - Sayın Özel, Gülsüm; Okutan, Yener; Oğuz Ahmet, Bebek Serra; Özdere, Eda (Mary Ann Liebert Inc., 2019)
Objective: This study compared the effects of different surface treatments on the surface roughness (Ra), and shear bond strength (SBS) of resin cement to yttria-stabilized tetragonal zirconia (Y-TZP) ceramic and nickel-chromium (Ni-Cr) base metal alloy, respectively. Materials and methods: Thirty disk-shaped specimens (3 mm height and 10 mm diameter) of each material (Y-TZP and Ni-Cr) were prepared. Both zirconia and metal specimens were randomly assigned to three equal groups, according to the surface treatments (n = 10): sandblasting, sandblasting + Er:YAG laser, and sandblasting + Nd:YAG laser. Resin cement cylinders (4 mm diameter and 3 mm thickness) were placed on each specimen. The SBS tests were performed at a 1 mm per minute crosshead speed through a knife-edge rod after 5000 thermal cycles. The Ra (?m) of the specimens was measured using a profilometer and evaluated topographically by atomic force microscopy and scanning electron microscopy. Analysis of variance, followed by Tukey's honestly significant difference, in addition to the Kruskal-Wallis test, followed by the Mann-Whitney U test, were used for statistical analysis (? = 0.05). Results: Combined sandblasting and laser treatment of the metal groups led to statistically higher Ra values than sandblasting alone (p < 0.05). For Y-TZP, there were no significant differences between the Ra values of the subgroups (p > 0.05). The SBS of the sandblasted metal group was significantly higher than the other two laser-irradiated groups, whereas the SBS of sandblasted zirconia was only significantly higher than the Nd:YAG laser-irradiated group (p < 0.05). Conclusions: Combined laser and sandblasting surface treatments resulted in rougher surfaces than sandblasting alone, especially for the metal specimens. Sandblasting, alone, improved the SBS of resin cement in both metal and zirconia, compared with the laser and sandblasting treatments, combined.
Keywords: Laser Irradiation; Sandblasting; Shear Bond Strength; Surface Topography